PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA PT. SANDABI INDAH LESTARI – PKS KETAHUN BENGKULU UTARA - Nur Arvian Eka Putra; Mimi Kurnia Nengsih (UM. Bengkulu, 2026)
In general, human resources are one of the most important factors and cannot be separated from an organization, both institutions and companies. This study aims to determine how organizational culture and transformational leadership influence employee performance at PT. Sandabi Indah Lestari-PKS, Ketahun. The type of research used is a quantitative method. The sample of this study was all employees at PT Sandabi Indah Lestari-PKS, Ketahun, North Bengkulu, totaling 120 people. The data analysis techniques used were quantitative descriptive analysis and inferential analysis. Based on the results of the study, it is known that 1). Organizational culture has a significant effect on employee performance at PT.Sandabi Indah Lestari PKS, Ketahun, North Bengkulu. 2). Transformational leadership style has a significant effect on employee performance, PT. Sandabi3). Organizational culture and transformational leadership have a significant influence on employee performance at PT. Sandabi Indah Lestari - PKS, Ketahun, North Bengkulu. Keywords : Employee Performance, Organizational Culture, Transformational Leadership.